CO2 reduction through low cost electrification of the diesel powertrain at 48V - Milton, Gareth; Blore, Paul; Tufail, Khizer; Coates, Barnaby Paul; Newbigging, Ian; Cooper, Allan; Shayler, Paul J. (Society of Automative Engineers, 2017)
In order to achieve fleet average CO2 targets, mass market adoption of low CO2 technologies is required. Application of low cost technologies across a large number of vehicles is more cost-effective in reducing fleet CO2 than deploying high-impact, costly technology to a few. Therefore, to meet the CO2 reduction challenge, commercially viable, low cost technologies are of significant interest. This paper presents results from the ‘ADEPT’ collaborative research program which focuses on CO2 reduction through the application of intelligent 48V electrification to diesel engines for passenger car applications. Results were demonstrated on a C-segment vehicle with a class-leading 4-cylinder 1.5 litre Euro 6 diesel engine. Electrification was applied through a high power, high efficiency, switched reluctance belt integrated starter generator (B-ISG) capable of both generation and motoring, and an Advanced Lead Carbon Battery for energy storage. The conventional alternator was replaced with a highly efficient DC-DC converter to supply energy to the 12V system. These technologies enabled powertrain efficiency improvement through the recovery of kinetic energy with regenerative braking and reapplication of the recovered energy through motoring to offset fuel usage. Efficiency was further optimised through application of engine downspeeding and advanced auto-stop strategies to extended engine-off time. Additional electrification was investigated through 48V ancillaries, including water-pump and air-conditioning compressor, and a turbo-compound generator for waste heat recovery from exhaust gas. These technologies have demonstrated a combined CO2 reduction of 10–11% against the conventional vehicle baseline. Additional studies of advanced thermal systems for improved warm-up, and lubrication control for FMEP reduction have also been conducted on this program. These indicate that by applying intelligent electrification to ancillaries a further 3–4% reduction in CO2 is achievable. Overall, this program shows that 48V technologies can achieve CO2 savings with a lower cost per gram CO2 than full hybrid solutions.